2016
DOI: 10.1002/app.43738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing condition and carbon nanotube on mechanical properties of injection molded multi‐walled carbon nanotube/poly(methyl methacrylate) nanocomposites

Abstract: In this work, multi‐walled carbon nanotubes (MWCNT) and poly(methyl methacrylate) (PMMA) pellets were compounded via corotating twin‐screw extruder. The produced MWCNT/PMMA nanocomposite pellets were injection molded. The effect of MWCNT concentration, injection melt temperature and holding pressure on mechanical properties of the nanocomposites were investigated. To examine the mechanical properties of the MWCNT/PMMA nanocomposites, tensile test, charpy impact test, and Rockwell hardness are considered as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…As can be seen, the slopes of the force curves largely depend on the composition of the samples, becoming higher the higher the amount of nanofiller. These results point out, therefore, that the higher the nanotube content, the higher the stiffness, in accordance with the results obtained by performing other mechanical tests, such as conventional strain–stress tests, which give information at the macroscopic level . Taking into account that the fibers here studied have similar values of roughness and curvatures and that they should have similar contributions from the possible existence of adhesion forces (other factors that may affect indentation curves), it can be concluded that the incorporation of carbon nanotubes reinforces the PVDF at the nanoscale, and most likely the main cause of the corresponding macroscopic mechanical reinforcement.…”
Section: Resultssupporting
confidence: 88%
“…As can be seen, the slopes of the force curves largely depend on the composition of the samples, becoming higher the higher the amount of nanofiller. These results point out, therefore, that the higher the nanotube content, the higher the stiffness, in accordance with the results obtained by performing other mechanical tests, such as conventional strain–stress tests, which give information at the macroscopic level . Taking into account that the fibers here studied have similar values of roughness and curvatures and that they should have similar contributions from the possible existence of adhesion forces (other factors that may affect indentation curves), it can be concluded that the incorporation of carbon nanotubes reinforces the PVDF at the nanoscale, and most likely the main cause of the corresponding macroscopic mechanical reinforcement.…”
Section: Resultssupporting
confidence: 88%
“…Polymeric nanocomposites are made of polymer matrix and filler at the nanoscale [3]. Literature shows that nanoscale reinforcing agents produce new mechanical and physical properties, which create a new class of nanocomposites [4]. In dentistry, many attempts have been made to create an improved version of PMMA with the addition of different nanosized fillers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocarbon fillers owing to their lightweight, high thermal conductivity and high aspect ratio are receiving significant attention. [6][7][8][9][10][11][12] Among them, graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) due to their two-dimensional (2D) and one-dimensional (1D) structure and ultrahigh surface areas offer exceptional thermal conductivity to the polymer nanocomposites. [13] Thermal conductivities of CNTs and graphene have been informed to reach in the range of 1950 to 5000 and 3000 to 6500 W/m K, respectively.…”
Section: Introductionmentioning
confidence: 99%